Characterizing posture and associated physiological demand during evacuation. (April 2018) - Cao, Li; Davis, Gerard A.; Gallagher, Sean; Schall, Mark C.; Sesek, Richard F.
Highlights: Physiological responses dramatically increase after crawling about 20 s. Average maximum crawling distance maybe incongruent with exit design criteria. Gender has a significant effect on crawling velocity and distance. Abstract: Crawling is recommended for accessing breathable air and avoiding gases during severe fire evacuations. Few studies have evaluated the physiological burden associated with crawling, but those that have agree that crawling places high physiological demands on the body. Furthermore, with the exception of walking upright, the effect of locomotion modalities on the speed of evacuation is sparsely researched. This study evaluated distance, velocity, and the physiological costs of evacuating using different locomotion methods. Twenty-four (24) college students (12 M/12F) traveled up to 91.44 m (m) in different postures: Upright Walking (UW), Stoop-Walking (SW), Foot and Hand Crawling (FHC), Knee and Hand Crawling (KHC), and Low Crawling (LC). Crawling velocities were significantly slower than bipedal velocities ( p  < 0.05). Of the three crawling postures, FHC was faster ( p  < 0.05) than both KHC and LC. Average velocities for FHC, KHC, and LC were 1.20, 0.84, and 0.77 m/s (m/s), respectively. Velocities in all crawling postures decreased substantially after the first 9.14 m of travel. The average maximum crawling distance measured in this study was<76.2 m. Physiological results demonstrated that crawling was more physically demanding than walking, represented by higher heart rates (HR), rates of oxygen consumption (VO2 ), ventilation rates (VE ), and respiratory exchange ratios (RERs). Crawling was perceived by subjects to be much more difficult than walking, with many subjects unable to complete the 91.44 m course. Results of this study should be considered in the evaluation of current evacuation recommendations and in the design of future evacuation routes.